Ubiquitous cardiology emerging wireless telemedical applications - Augustyniak, Piotr, 1965- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
The Internet and other technological developments are now playing increasing roles in consumer health and the delivery of health services. This book provides developmental solutions and explanations for cardiovascular diagnostics. Useful to field researchers, academicians, and healthcare practitioners, this Premier Reference Source presents a collection of studies on medical data redundancy, priority, and validity.